Assessment of MC2010 and AS3600 models for estimating instantaneous flexural crack widths in fibre reinforced concrete members. (1st April 2020) - Bernard, E.S.; Amin, A.; Gilbert, R.I.
Highlights: Addition of fibres to concrete may reduce the spacing and width of flexural cracks. Measured results are compared to predictions to two structural concrete codes. Incorporating bond strength between steel and FRC results in improved predictions. Abstract: The inclusion of fibres into concrete is now an accepted method of controlling crack widths. Several recently released design guidelines and codes of practice contain provisions which allow designers to predict the instantaneous crack widths in reinforced concrete members (containing fibre reinforcement) subjected to flexure. Most of these models have been developed for steel fibres, despite non-steel fibres representing a significant proportion of the fibres available in the marketplace. The current paper examines the results of flexural tests on 53 sets of beams reinforced with steel bars and fibre reinforced concrete. The specimens contained a wide range of fibre types, including steel, polypropylene, aramid, glass, basalt & PVA fibres. An assessment of available codified expressions for crack width estimation has been compared to measured crack widths presented herein. Despite satisfactory results, improved comparisons may be obtained by using the residual tensile strength of fibres at crack widths substantially smaller than is normally used, and by considering alternative expressions for the bond strength between steel reinforcing bars and fibre-concrete than are presently used in code models.